Zmiany w orzecznictwie sądów administracyjnych w sprawie dostępu do dokumentacji związanej z dowodem osobistym - Zachariasz, Wojciech (Studia Prawa Publicznego, 2025)
The article undertakes an analysis of the jurisprudence of administrative courts in the scope of providing access to documentation related to an identity card, with particular emphasis on Article 75 of the Act of 6 August 2010 on identity cards. The first part of the paper discusses the clerical practice in the scope of providing access to personal data and interpretational discrepancies concerning the legal basis for access to this information, indicating the application of Articles 23 and 24 of the Civil Code in the context of the protection of personal rights. It is critically pointed out that public administration bodies inconsistently and erroneously apply the provisions, considering the cult of memory of a deceased person as the basis for access to the documentation in question. In the main part, selected judgments of provincial administrative courts are analysed, and attention drawn to erroneous approaches to interpreting the provisions on access to documentary evidence. Particular attention is given to judgments in which the courts replicated the form and manner of transfer of records adopted in clerical practice to entities that showed only an emotional bond with the deceased whose documents were requested. The final part of the article presents a landmark decision of the Supreme Administrative Court, which set the right direction for the interpretation of the provisions on the provision of documentation and pointed to the hitherto misinterpretation of Article 75 of the identity cards and Articles 23 and 24 of the Civil Code.